Mechanism of streptomyces albidoflavus STV1572a derived 1-heneicosanol as an inhibitor against squalene epoxidase of Trichophyton mentagrophytes. (May 2021) - Thekkangil, Aswani; George, Benu; Prakash, S.M. Udaya; Suchithra, T.V.
Abstract: An increase in incidences of tinea infections paves the way to discover the novel antifungal drugs from unexplored natural resources. The quality of life in patients with tinea infection may be affected by different factors, including morbidity, length of illness, social and demographic factors. The present investigation explores the functional principle of a bioactive compound isolated from actinomycetes, S. albidoflavus STV1572a by in-silico and in-vitro studies. In continuation of our previous reports on the antidermatophytic potential of S. albidoflavus STV1572a, this study progresses with the in-silico molecular docking study of the seven GC-MS discovered ligands, and six dermatophytic modelled targets. Through virtual screening, it was revealed that a docking score −8.8 between 1-heneicosanol and squalene epoxidase favored partially in understanding the mode of action. Further validation of in-silico study was performed by a sterol quantification assay which confirmed the antidermatophytic mechanism of 1-heneicosanol. Taken together, the evidence from this study suggests that 1-heneicosanol has a potential antidermatophytic compound and can be considered for dermatophytic treatment. Graphical abstract: Image 1 Highlights: T. mentagrophytes are zoophilic fungi and its infection demands prolonged medical attention. This study explores the mechanism of the bioactive compounds from S. albidoflavus STV1572a against T. mentagrophytes . Fewer reports on T. mentagrophytes motivates to in-silico and in-vitro study for a potent antidote. This investigation establishes 1-henecosinol inhibition of squalene epoxidase by blocking ergosterol biosynthesis.